The formalization of geometrical, calculation and tehnological informations as the base for CAD/CAM oriented programming systems - Gatalo, Ratko; Hodolič, Janko; Zeljković, Milan; Borojev, Ljubomir; Rekecki, Jožef (Journal of Production Engineering, 1984)
In this paper an up-to-date concept of CAD/CAM oriented symbolic language SAPOR is presented. SAPOR introduces the foralizations of geometrical, computational and tehnological informations immanent to individual or integral programming systems for automatic calculation, construction and technological design of procedures for NC or conventional machine tools. Besides the symbolic structures, based on serbo-creation language and its individual characteristics and features, there are some aspects of its modification due to foreign languages implementation and posibitities of interactive compozition of input pharameters in alpha-numeric and graphic form underlined. Also, some aspects of reduction of input informations incase of standards and recomandations usage are particulary underlined.